Loop-mediated isothermal amplification (LAMP) assays for detection of the New Guinea fruit fly Bactrocera trivialis (Drew) (Diptera: Tephritidae) - Melissa L. Starkie; Elizabeth V. Fowler; Xiaocheng Zhu; Arati Agarwal; Lea Rako; Isarena C. Schneider; Mark K. Schutze; Jane E. Royer; David Gopurenko; Peter Gillespie; Mark J. Blacket (Scientific Reports, 2022)
Abstract The cue-lure-responding New Guinea fruit fly, Bactrocera trivialis, poses a biosecurity risk to neighbouring countries, e.g., Australia. In trapping programs, lure caught flies are usually morphologically discriminated from non-target species; however, DNA barcoding can be used to confirm similar species where morphology is inconclusive, e.g., Bactrocera breviaculeus and B. rufofuscula. This can take days—and a laboratory—to resolve. A quicker, simpler, molecular diagnostic assay would facilitate a more rapid detection and potential incursion response. We developed LAMP assays targeting cytochrome c oxidase subunit I (COI) and Eukaryotic Translation Initiation Factor 3 Subunit L (EIF3L); both assays detected B. trivialis within 25 min. The BtrivCOI and BtrivEIF3L assay anneal derivatives were 82.7 ± 0.8 °C and 83.3 ± 1.3 °C, respectively, detecting down to 1 × 101 copies/µL and 1 × 103 copies/µL, respectively. Each assay amplified some non-targets from our test panel; however notably, BtrivCOI eliminated all morphologically similar non-targets, and combined, the assays eliminated all non-targets. Double-stranded DNA gBlocks were developed as positive controls; anneal derivatives for the COI and EIF3L gBlocks were 84.1 ± 0.7 °C and 85.8 ± 0.2 °C, respectively. We recommend the BtrivCOI assay for confirmation of suspect cue-lure-trapped B. trivialis, with BtrivEIF3L used for secondary confirmation when required.